2021
DOI: 10.3389/fmars.2021.645531
|View full text |Cite
|
Sign up to set email alerts
|

Strain Evolution and Instability of an Anticyclonic Eddy From a Laboratory Experiment

Abstract: Using the 13 m diameter LEGI-Coriolis rotating platform, the evolution processes of a generated anticyclonic eddy throughout its lifecycle are analyzed. Experimental results have shown that the eddy lasted for approximately 3T0, where T0 is the rotating period of 90 s. After T = 0.3T0, the eddy enters its mature phase, whereby following this event, eddy intensity slowly decreases from its maximum rotation speed. By T = 2.6T0, the eddy enters a stage of rapid weakening. In its decay period, two underlying mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Eddy merging plays a significant role in cross-scale energy transfer and the marine ecological environment [19,20]. Meanwhile, the process of eddy merging has important implications for the dynamics of eddy pairs [21,22], the non-linear equilibrium [23], and the life span of eddies [24]. Zhai et al [25] simulated a large number of westward-propagating eddies in the ocean and found that eddy merging can cascade energy to larger scales, eventually dissipating at the western boundary.…”
Section: Introductionmentioning
confidence: 99%
“…Eddy merging plays a significant role in cross-scale energy transfer and the marine ecological environment [19,20]. Meanwhile, the process of eddy merging has important implications for the dynamics of eddy pairs [21,22], the non-linear equilibrium [23], and the life span of eddies [24]. Zhai et al [25] simulated a large number of westward-propagating eddies in the ocean and found that eddy merging can cascade energy to larger scales, eventually dissipating at the western boundary.…”
Section: Introductionmentioning
confidence: 99%